Renal allograft DARCness in subclinical acute and chronic active ABMR. (25th June 2021) - Kläger, Johannes; Eskandary, Farsad; Böhmig, Georg A.; Kozakowski, Nicolas; Kainz, Alexander; Colin Aronovicz, Yves; Cartron, Jean‐Pierre; Segerer, Stephan; Regele, Heinz
Summary: Gene expression profiling of renal allograft biopsies revealed the Duffy antigen receptor for chemokines (DARC) as being strikingly upregulated in antibody‐mediated rejection (ABMR). DARC has previously been shown to be associated with endothelial injury. This study aimed at assessing the value of DARC immunohistochemistry as diagnostic marker in ABMR. The study was performed on 82 prospectively collected biopsies of a clinically well‐defined population (BORTEJECT trial, NCT01873157) of DSA‐positive patients with gene expression data available for all biopsies. Diagnostic histologic assessment of biopsies was performed according to the Banff diagnostic scheme. DARC expression was focally accentuated, on peritubular capillaries (PTC) mostly in areas of interstitial fibrosis and/or inflammation. DARC positivity was associated with diagnosis of ABMR and correlated with DARC gene expression levels detected by microarray analysis. Still, as previously described, a substantial number of biopsies without signs of rejection showed DARC‐positive PTC. We did not observe significantly reduced graft survival in cases showing histologic signs of ABMR and being DARC‐positive, as compared to DARC‐negative ABMR. In summary, the upregulation of DARC, detected by immunohistochemistry, is associated with but not specific for ABMR. We did not observe reduced graft survival in DARC‐positive patients.